Programming the web : - Sosinsky, Barrie A. (McGraw-Hill Technology Education, 2004)
PROGRAMMING THE WEB by Barrie Sosinsky is designed for the 1st course in a web-programming curriculum. Students will first be exposed to the fundamentals of web programming that are used in the majority of the languages covered. It will then undercover to students the following languages: HTML, XML, Java, JavaScript, ASP, and Perl /CGI. This book ultimately lays the basic foundation for web programming